Evaluation of Novel Microabrasion Paste as a Dental Bleaching Material and Effects on Enamel Surface. Issue 5 (20th December 2014) - Bağlar, Serdar; Çolak, Hakan; Hamidi, Mehmet Mustafa; Paravina, Rade
Abstract Purpose Dental fluorosis is an enamel dysplasia that can cause serious aesthetic and psychological problems. An examination of the literature shows that the microabrasion method is the most effective way to treat fluorosis. This study aimed to produce a prototype microabrasion paste for the treatment of fluorosis stains and to examine the effects of the paste on tooth structure and color in vitro. Material and Methods Forty extracted upper incisor teeth were used in this study. The teeth were divided into four treatment groups: a prototype microabrasion paste group (N = 10), an Opalustre paste group (N = 10), a 37% phosphoric acid gel group (N = 10), and a distilled water (control) group (N = 10). Following treatment, all specimens in each of the four groups were examined by scanning electron microscopy for changes in their surface enamel. Changes in tooth color changes of the 1st and 2nd groups were measured before and after treatment by a VITA Easyshade Advance spectrophotometer. Results In scanning electron microscopy evaluations, significant differences were not observed between the 1st and 2nd groups. Differences in three color‐measuring coordinates between the 1st and 2nd were also not statistically significant (p > 0.05). Conclusions The study demonstrated that the prototype paste is a viable treatment option for dental fluorosis. Clinical Significance The findings in this study demonstrated that the tested prototype microabrasion paste is extremely harmless, minimally invasive agent, and able to improve the color, shine and chrome values of the teeth.